Effectiveness of combined techniques vs passive recovery in competitive squash players: A crossover study - Wilder Geovanny Valencia-Sánchez; Jorge M. Celis-Moreno; Nelson Esteban Valle Graciano (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Objective: This study examined the effects of two recovery techniques, combined techniques and passive recovery, on physiological, neuromuscular, and psychophysiological performance in competitive squash players during three days of simulated matches.